Unpaired socks in a dark room. Probability calculation materials for teachers in primary and secondary schools - Brunelli, Fabio; Chesi, Francesco (EDiMaST: Experiences of Teaching with Mathematics, Sciences and Technology, 2018)
The authors report a probability training course for primary and high school teachers. With the theoretical references, the contribution includes materials and proposals for activities to be carried out in the classroom.